2006
DOI: 10.1136/jcp.2006.037853
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of low-grade and high-grade prostate carcinoma: relative changes of parathyroid hormone-related protein and its parathyroid hormone 1 receptor, osteoprotegerin and receptor activator of nuclear factor-kB ligand

Abstract: All the evaluated factors are overexpressed mainly in the high-grade tumours. Our findings indicate that, in most patients with PCa (with Ki67 values between 1% and 9%), sequential determination of C-terminal PTHrP and RANKL immunoreactivities is a useful approach to discriminate low-grade and high-grade tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
2
19
0
1
Order By: Relevance
“…The effects of PTHrP have been studied in tumor and normal tissues, including bone, prostate, skin, heart and lung [11,[20][21][22]. However, the exact role of the PTHrP in the urinary bladder is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of PTHrP have been studied in tumor and normal tissues, including bone, prostate, skin, heart and lung [11,[20][21][22]. However, the exact role of the PTHrP in the urinary bladder is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have failed to correlate serum RANKL or OPG levels with presence of bone disease or survival (reviewed in [42]). In prostate cancer, increased RANKL expression has been observed in primary and bone metastatic tumor cells, with increased expression in metastatic tumors compared with primary tumors [37,44,45]. In separate studies, levels of serum RANKL have not been observed to increase in prostate cancer patients [46,47].…”
Section: Regulation Of Rankl and Opg Expression In Cancermentioning
confidence: 95%
“…An extensive review of the literature indicates that hypercalcemia is exceptionally rare in prostate cancer, occurring in <2% of cases (37,38). PTH and PTH-related protein are immunologically distinct proteins that bind with equal affinity to the PTH-IR, which is highly expressed on prostate cancer bony metastases (39 (41). This suggests that an increased sensitivity of prostate cancers to PTH also may contribute to the progression of metastases in bone.…”
Section: Pth Promotes the Proliferation And Migration Of Prostate Canmentioning
confidence: 99%